2023
DOI: 10.1177/21582440231177298
|View full text |Cite
|
Sign up to set email alerts
|

Class participation and feedback as enablers of student academic performance

Abstract: In an educational context focused on student learning, class participation and feedback are key to improving students’ performance. Class participation grading methods are often unclear and subjective, therefore, providing feedback on class participation grades is challenging for lecturers. In this study, the Work-In-Class Assessment Tool (WICAT) designed by researchers is a multidimensional system that grades class participation by assessing students’ attendance, active listening, contribution to class activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Web-based student response systems enable students to respond to teachers' questions, receive feedback, and view their classmates' responses in real-time, thereby enhancing interactivity in the classroom and giving students room to self-assess (Heaslip et al, 2013;Persaud and Persaud, 2019). This is beneficial since researchers have highlighted the critical role of timely feedback in assessing class participation (Márquez et al, 2023), to allow students to engage in corrective actions (Macfarlane, 2016). These web-based systems are also ideal for use in large classes where time constraints are often an issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Web-based student response systems enable students to respond to teachers' questions, receive feedback, and view their classmates' responses in real-time, thereby enhancing interactivity in the classroom and giving students room to self-assess (Heaslip et al, 2013;Persaud and Persaud, 2019). This is beneficial since researchers have highlighted the critical role of timely feedback in assessing class participation (Márquez et al, 2023), to allow students to engage in corrective actions (Macfarlane, 2016). These web-based systems are also ideal for use in large classes where time constraints are often an issue.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are barriers to objectively assessing class participation. A seminal article by Armstrong and Boud (1983) discussed the problems commonly encountered in grading participation, and evidence suggests that most of these problems in assessing participation persist at present (Márquez et al, 2023). Some of the challenges include subjectivity, reliability, and the unintended detrimental effect of some methods of assessment used by instructors on the quality of class discussions (Armstrong and Boud, 1983;Bean and Peterson, 1998;Xu and Qiu, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Arum Putri Rahayu students who rank in the class, although not specifically mentioned, it showed that they really put the high efforts to master each subject studied." (Mamoon-Al-Bashir et al, 2016), (Márquez et al, 2023) suggests that grades are essential for providing feedback to students, and when grading is specific to the content being taught, it can lead to improved performance. Gray & Diloreto, (2016) found that students who received comments tailored to their performance showed a significant increase in their scores on a task, while those who received only grades or both grades and comments experienced declines in their scores.…”
Section: To What Extent Do the Teachers Assess Students' Listening Co...mentioning
confidence: 99%